An Overview of the Situation of SMEs in Hungary in Catching up to Industry 4.0 - Popovicsné Szilágyi, Zita (International Journal of Engineering and Management Sciences, 2022)
Since I have been working I have been in contact with small and medium-sized enterprises (SMEs) and large companies in various ways. I have thus been confronted with the disadvantages of the former in terms of the introduction and use of 4IF technologies. Yet most of them are aware that to remain competitive in the market, they cannot avoid digitising their operational processes to some extent. I have also found that this mainly depends on the characteristics of the organisation; for example, its orientation. Domestic SMEs are therefore currently at a competitive disadvantage in the market. However, there is no information on whether there is a trend towards development and where they themselves should develop. This would help them to develop the right, achievable vision for the future, coupled with a feasible business strategy.